Theoretical domains of exploring energy security as a global challenge in international relations - Mišev, Gordana (Sociološki pregled, 2020)
From the first discoveries of fossil fuels in the late nineteenth century to the present, the importance of energy resources has been gaining global proportions, not only in economic, political and social terms, but has become an indispensable aspect of national and international security. Energy has become an important factor in international cooperation (gas pipelines, oil pipelines), but also of open and covert conflicts and tensions (oil shocks, gas crises, economic sanctions). The work analyzes the development of theoretical directions for post-Second World War security studies and its weaknesses in understanding the importance and role of energy security in complex international relations. The aim of the work is to analyze and explain energy resources as an important factor of national and international security and its interdependence and complexity of economic, military, political, social and ecological phenomena with the aid of sector theory and global sociological approach.
Keywords: international relations; energy resources; security; conflicts; security of supply